Exploring the Foundations for Developing a “Historical Value Pedagogy” Model: The Role of History of Islamic Culture (SKI) Learning in Students’ Internalization of Islamic Values - Alfaridzih, Achmad; Naih Al Hashas, Mohammad; Eka Yudesthira, Redy; Kurniawan, Desi; Wulansari, Devi (Program Studi Doktor Pendidikan Agama Islam dan Program Magister Pendidikan Agama Islam, Pascasarjana Universitas Islam Negeri Sunan Ampel, 2026)
Abstract: This study aims to analyze the contribution of Sejarah Kebudayaan Islam (SKI) learning to the internalization of Islamic values among students and to explain the underlying pedagogical–psychological mechanisms as a basis for formulating the Historical Value Pedagogy model. The study employs a mixed methods approach with a sequential explanatory design, combining quantitative analysis through Structural Equation Modeling (SEM) and qualitative analysis through in-depth interviews. The findings indicate that SKI learning has a positive effect on value internalization, although within a weak category, while its influence on psychological processes is relatively stronger. Psychological processes function only as a partial mediator with limited contribution, resulting in suboptimal value internalization. Qualitative findings reveal that learning remains dominated by a cognitive approach and is not sufficiently supported by reflection and habituation, preventing students’ affective responses from developing into behavioral outcomes. This study concludes that value internalization requires an integrative and transformative pedagogical approach. Accordingly, the *Historical Value Pedagogy* model is proposed, integrating historical understanding, affective engagement, reflection, habituation, and behavioral actualization as a framework for strengthening SKI learning.